Wives behaving badly - Buchan, Elizabeth (New York : Viking, 2006)
What happens when the mistress becomes the wife? Minty Lloyd is now the second wife to her husband, Nathan--but she is shunned by his friends, despised by his grown children, and haunted by her very much alive, and quite reborn, predecessor Rose. Yet after a shocking phone call, Minty finds herself united with an unexpected ally--the woman she once betrayed.--From publisher description.
Sequel to: Revenge of the middle-aged woman.
Keywords: Middle-aged women -- Fiction; Middle-aged mothers -- Fiction; England -- Fiction; Domestic fiction